Desenvolvimento e implementação de uma ferramenta facilitadora para determinação dos limites de resíduo de ativo utilizados na validação de limpeza das plantas produtivas de uma indústria farmacêutica - Sousa, Maria Mayara Saraiva de (2023)
Within the pharmaceutical industry there are good manufacturing practices (GMP) that are part of Quality Assurance that ensure that products are consistently produced and evaluated, ensuring appropriate quality standards for the intended use and required by registration. Cleaning validation is a fundamentally important parameter in industrial production processes, since they are essential to prevent the occurrence of cross contamination between batches of different actives, detergent residues and microbiological contamination. The main objective of this work is to determine the acceptance limits of the active used in the cleaning validation of the productive plants of a large Pharmaceutical Industry. The acceptance limit, a real numeric value whose calculation takes into account the batch size, dose of the researched active, subsequent product, toxicological data, solubility and contact area of the product with the equipment, is one of the essential criteria of the validation protocol of cleaning. The limits must be practical, verifiable, achievable and must be defined using scientific criteria with theoretical and coherent basis to ensure that they were defined correctly, without jeopardizing the calculations performed later. With the correct determination of the worst-case product acceptance criteria for each production line, it is possible to minimize the risk of cross-contamination and consequently increase the reliability, safety and effectiveness of the products supplied by the pharmaceutical industries. The present work was of great relevance, since, in addition to reviewing the calculations of residual assets practiced, it brought a technical-scientific foundation, feeding a reliable database through references. In this way, throughout the life cycle of the product, the limit determined as an acceptance criterion will have a foundation and traceability, increasing the reliability of the results presented to regulatory agencies and facilitating the changes that occur with the product over time.